2010
DOI: 10.1186/1479-5868-7-19
|View full text |Cite
|
Sign up to set email alerts
|

Causal beliefs about obesity and associated health behaviors: results from a population-based survey

Abstract: BackgroundSeveral genetic variants are associated with obesity risk. Promoting the notion of genes as a cause for obesity may increase genetically deterministic beliefs and decrease motivation to engage in healthy lifestyle behaviors. Little is known about whether causal beliefs about obesity are associated with lifestyle behaviors. Study objectives were as follows: 1) to document the prevalence of various causal beliefs about obesity (i.e., genes versus lifestyle behaviors), and 2) to determine the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 37 publications
(37 reference statements)
4
73
0
1
Order By: Relevance
“…This particular belief is directly linked to the causal attribution of obesity or underweight, that is, it can be an answer to the "Why don't I meet weight standards" question. Exploring this issue from a health communication and information point of view could prove a fruitful field of research (Hilbert et al, 2009;Wang & Coups, 2010). Moreover, the belief that the body is not malleable (i.e., is genetically driven) has consequences on self-blame ) and thus on the dieting process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This particular belief is directly linked to the causal attribution of obesity or underweight, that is, it can be an answer to the "Why don't I meet weight standards" question. Exploring this issue from a health communication and information point of view could prove a fruitful field of research (Hilbert et al, 2009;Wang & Coups, 2010). Moreover, the belief that the body is not malleable (i.e., is genetically driven) has consequences on self-blame ) and thus on the dieting process.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, as far as we know, only one study has ever explored the consequences of causal attribution of weight on behavior. Wang and Coups (2010) explored beliefs about obesity within the general population and found that believing that the cause was genetic produced less healthy behaviors. The present study manipulated this variable in order to elucidate the relationship between beliefs about malleability, body perception and consequent behavior.…”
Section: Body Malleability Beliefsmentioning
confidence: 99%
“…For example, belief in genetic causality for cardiovascular disease, obesity, or cancer has been reported to be associated with less preventive behaviors, more risky behaviors, greater belief in biological treatment effectiveness, or less perceived control (Claassen et al, 2010;Kaphingst, Lachance, & Condit, 2009;Senior & Marteau, 2007;Senior, Marteau, & Peters, 1999;Wang & Coups, 2010). A recent meta-analysis, however, concluded that the evidence for such fatalism in response to genetic testing is limited (Collins, Wright, & Marteau, 2011).…”
Section: Potentially Negative Correlates Of Threat Representationsmentioning
confidence: 99%
“…The second condition would be met if patients' representations of T2D include the belief that the threat can be addressed (i.e., the illness can be prevented, even in the face of genetic risk) through appropriate coping strategies such as dietary improvements, exercise, or medication. In contrast, genetic information might result in fatalistic beliefs that T2D cannot be prevented at all (Claassen et al, 2010), or in discounting of behavioral treatment strategies among people with high behavioral risk (O'Neill, McBride, Alford, & Kaphingst, 2010;Wang & Coups, 2010). Such fatalistic beliefs may manifest as less physical activity and poorer diet habits among people with representations that include genetic causality.…”
mentioning
confidence: 99%
See 1 more Smart Citation